ANALISIS KUALITAS BUTIR SOAL PADA BANK SOAL BIOLOGI KELAS X SMA - KRISAININ RAHMADHANI, ERLIAN (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
Writing biology tests for Grade X, the biology teachers of SMA Negeri 2 Mejayan do not perform a qualitative review maximally before they apply them as a test instrument for their students. This shows that the biology teachers of SMA Negeri 2 Mejayan do not apply the procedure of how to write tests in accordance with the standard. This thesis is aimed to know the logical validity dealing with the aspects of materials, constructions, and languages, and revise the tests to make them more valid. This thesis took use of Deskriptive Qualitative Method. The samples of Biology-Test Bank were determined by Purposive Sampling Technique. Meanwhile, data were collected using Documentation Method. The logical validity was qualitatively reviewed based on aspects in the instrument. The review reveals that most multiple-choice tests are suitable to the aspects of materials, constructions, and languages. Some items need revision for the aspect of constructions. All of essay-tests meet all the aspects of review. Therefore, most test items have good logical-validity because they fulfill standard needs, but some items need to be revised for the aspect of constructions. The revision have been done, so that all test items are valid and suitable to an acceptable standard Keywords: qualitative analysis, test bank, logical validity.